OPTIMIZATION OF THE POLYMER-POWDERED BEARINGS CONTACTING CONDITIONS - Konstantin G. SHUCHEV; Ilya A. ZORIYEV; Igor V. OVECHKIN; Maria S. SHEVTSOVA; Sergey I. IVANOV (Advanced Engineering Research)
Optimal correlation between polymer and metal-ceramic areas in the friction zone is established for the developed construction of polymer-powdered bearings with a combined working surface that can hold the grease contained in the metal matrix pores.